(untitled) (Quest Journal of Management and Social Sciences, 2024)
Background: Making a career decision is a crucial moment in any student’s life. A good career decision leads to bridge the gap between where you are and where you want to be. Identification of the factors that influence student’s career decision making helps them to achieve their goal. Objective: Therefore, this study looks into MBA student’s perception towards their Career Choice. Method: The explanatory research design was adopted for this study based upon social cognitive theory. The study area of the research is Kathmandu valley where Structural questionnaires were used using KOBO toolbox to collect the data. Using the Stratified sampling methods, data were collected on a sample of 229 students pursuing MBA from different University. Structural Equation Modeling is used to see the MBA students’ perception towards career choice using SPSS and SPSS AMOS software. Finding: Findings reveal that the majority of the students were female, which suggests that lack of guidance, lack of experience, and financial circumstances are the main problems that may be overcome by good supervision as well as practical/experimental exposure to improve students’ career choices. Moreover, SEM result indicates that individual background and self-efficacy are significance causal relationship to career choice. Conclusion: The idea of career should be focused on freedom to do job in flexible timing and to get credit for result for idea and result. Factors such as Career advancement, status of the organization i.e. size, status and image are the major indicators for choice of career. Paper Types: Research Paper Keywords: Entrepreneurship, Employment, Career Choice, MBA program JEL Classification: C26, E24, M10, C12